Epigenetics in LMNA-related cardiomyopathy - Wang, Yinuo; Dobreva, Gergana (Cells, 2023)
Mutations in the gene for lamin A/C (LMNA) cause a diverse range of diseases known as laminopathies. LMNA-related cardiomyopathy is a common inherited heart disease and is highly penetrant with a poor prognosis. In the past years, numerous investigations using mouse models, stem cell technologies, and patient samples have characterized the phenotypic diversity caused by specific LMNA variants and contributed to understanding the molecular mechanisms underlying the pathogenesis of heart disease. As a component of the nuclear envelope, LMNA regulates nuclear mechanostability and function, chromatin organization, and gene transcription. This review will focus on the different cardiomyopathies caused by LMNA mutations, address the role of LMNA in chromatin organization and gene regulation, and discuss how these processes go awry in heart disease.